(untitled) (Architecture Image Studies, 2025)
The notion of Information Management (IM) is fundamental to the field of heritage building rehabilitation and preservation. Historically, preservation and reconstruction have been inadequately recorded, resulting in no standardization and education regarding past practices. This deficiency challenges fresh restoration efforts and the preventive maintenance of heritage components. This study presents the Design and Development of a Heritage Building Information and Maintenance Management System (DD-HBIMMS) for Architectural Heritage (AH). The HBIMMS literature emphasizes the necessity for additional research regarding the comprehensive operations of AH projects, their practical execution, and the requirement for improved cultural preservation. This study employs Design Science Methodology (DSM) to establish a protocol to enhance working processes in collaborative AH projects. HBIMMS is proposed as an online framework designed to store AH information and delineate operations. Consequently, a straightforward and visual HBIMMS protocol has been formulated and implemented in a practical case study.